Involving migrants in the development of guidelines for communication in cross-cultural general practice consultations: a participatory learning and action research project - O'Reilly-de Brún, Mary (BMJ Open, 2015)
OBJECTIVE: The aim of this research was to involve migrants and other key stakeholders in a participatory dialogue to develop a guideline for enhancing communication in cross-cultural general practice consultations. In this paper, we focus on findings about the use of formal versus informal interpreters because dialogues about these issues emerged as central to the identification of recommendations for best practice. DESIGN: This qualitative case study involved a Participatory Learning and Action (PLA) research methodology. PARTICIPANTS: The sample comprised 80 stakeholders: 51 from migrant communities; 15 general practitioners (GPs) and general practice staff; 7 established migrants as peer researchers; 5 formal, trained interpreters; and 2 service planners from the national health authority. SETTING: Galway, Ireland. RESULTS: There was 100% consensus across stakeholder groups that while informal interpreters have uses for migrants and general practice staff, they are not considered acceptable as best practice. There was also 100% consensus that formal interpreters who are trained and working as per a professional code of practice are acceptable as best practice. CONCLUSIONS: Policymakers and service planners need to work in partnership with service providers and migrants to progress the implementation of professional, trained interpreters as a routine way of working in general practice.